Magnoflorine from Coptis chinese has the potential to treat DNCB-induced Atopic dermatits by inhibiting apoptosis of keratinocyte. Issue 2 (15th January 2020) - Wu, Siqi; Yu, Deqing; Liu, Wuyang; Zhang, Jian; Liu, Xiaojiang; Wang, Jiankang; Yu, Min; Li, Zhaoxing; Chen, Qianfeng; Li, Xuegang; Ye, Xiaoli
Graphical abstract: Highlights: Magnoflorine from Rhizoma coptidis attenuated DNCB-induced atopic dermatitis-like symptoms in mice. Magnoflorine inhibited IFN-γ and TNF-α-induced apoptosis of HaCaT cell. Magnoflorine attenuated the expressions of apoptosis-related proteins in HaCaT cells. Magnoflorine increased mitochondrial membrane potential. Abstract: Aims: In Sheng Nong's herbal classic in China, Rhizoma coptidis a (RC) could be used to treat Atopic dermatits b (AD), but its core ingredient(s) and mechanism remains unknown. The present study aimed to find out the ingredients against AD and expound its mechanisms. Materials and methods: Seven alkaloids were isolated from RC to compare the inhibition against HaCaT cells by MTT assays and apoptosis of cells stimulated with TNF-α/IFN-γ by flow cytometry. The effects of target alkaloids against AD were evaluated on DNCB c (2, 4-dinitrochlorobenzene)-induced atopic dermatitis in mice. Key findings: Seven alkaloids were isolated from RC successfully. The results from MTT and flow cytometry indicated that among these alkaloids, only magnoflorine d (MAG) had no obvious toxicity on cells, but could inhibit the apoptosis of the cells stimulated with TNF-α/IFN-γ. Further animal experiments confirmed that MAG significantly attenuated the AD-like symptom and inhibited the AD-induced increases in IgE/IL-4, as compared with control (P < 0.01). Moreover, MAG reduced the low Δψm e (mitochondrial membrane potential) in HaCaT cells. The results of western blotting proved that MAG inhibited apoptosis of keratinocytes through decreasing the expressions of CTSB f (cathepsin B), Cyte C g (cytochrome C ), Bid and caspase-3/7/8/9. Significance: Overall, MAG inhibited apoptosis by decreasing the expression of apoptotic pathway-related proteins, and laid a foundation for the study of AD mechanisms.